Update lessons from positron emission tomography imaging part I: a systematic critical review on therapeutic plasma concentrations of antipsychotics - Hart, Xenia Marlene; Spangemacher, Moritz; Uchida, Hiroyuki; Gründer, Gerhard (Therapeutic drug monitoring, 2024)
Background: - Positron emission tomography (PET) and single photon emission tomography (SPECT) of molecular drug targets (neuroreceptors and transporters) provide essential information for therapeutic drug monitoring-guided antipsychotic drug therapy. The optimal therapeutic windows for D2 antagonists and partial agonists, as well as their proposed target ranges, are discussed based on an up-to-date literature search. - Methods: - This part I of II presents an overview of molecular neuroimaging studies in humans and primates involving the target engagement of amisulpride, haloperidol, clozapine, aripiprazole, olanzapine, quetiapine, risperidone, cariprazine, and ziprasidone. The systemic review particularly focused on dopamine D2-like and 5-HT2A receptors. Target concentration ranges were estimated based on receptor occupancy ranges that relate to clinical effects or side effects (ie, extrapyramidal side effects). In addition, findings for other relevant receptor systems were included to further enrich the discussion. - Results: - The reported reference ranges for aripiprazole and clozapine align closely with findings from PET studies. Conversely, for haloperidol, risperidone, and olanzapine, the PET studies indicate that a lowering of the previously published upper limits would be necessary to decrease the risk of extrapyramidal side effect. - Conclusions: - Molecular neuroimaging studies serve as a strong tool for defining target ranges for antipsychotic drug treatment and directing therapeutic drug monitoring.
Gesehen am 26.02.2024